Effect of dual-modification on some properties of rice starch based biodegradable films - Woggum, Thewika; Wittaya, Thawien (Food and Applied Bioscience Journal, 2017)
The properties and characteristics of native rice starch and dual-modified rice starch in relation to dual-modified rice starch films were investigated. In this study, the rice starch was hydroxypropylated with 6–12% of propylene oxide followed by crosslinking with 2% sodium trimetaphosphate (STMP). Increasing of propylene oxide concentrations in the dual-modified rice starch yielded an increase in the molar substitution (MS) and degree of substitution (DS) of the modified rice starch. However, the pasting temperature, paste consistency, breakdown, setback and gel strength showed an inverse trend. Biodegradable films were prepared from the dual-modified rice starch. The results showed that the maximum tensile strength (TS) was presented when using the 8% propylene oxide. The Elongation at break (%E) and film solubility (FS) of the films were higher than native rice starch and these tended to increase when the concentration of propylene oxide increased. However, the water vapor permeability (WVP) of the films was lower than the native rice starch and these did not significantly change with an increase in the concentration of propylene oxide (p>0.05).